The Humanities through the Lens of Migration: Richard Koebner’s Transition from Germany to Jerusalem - Feldhay, Rivka (Naharaim, 2017)
The present article turns the spotlight onto epistemic-normative dilemmas that, in my estimation, stand at the heart of the humanities as a field of study (the reason for the hyphen between epistemic and normative will become evident as we progress). For the sake of elucidating these productive tensions, we will delve into the thought of Richard Koebner (1885–1958) – a Jewish historian that emigrated from Germany to Palestine in 1934. This transition crystallized the above-mentioned dilemmas in his own mind, from both a personal and theoretical standpoint. More specifically, he developed a critical historiographic outlook on the past and present alike. A major focus of his deliberations was the nature of humanistic knowledge, not least historiography. Though this question preoccupied Koebner throughout his academic career, the new circumstances in Palestine/Israel sharpened and shaped his perspective.